Moderate Intensity Cycling Combined with Cognitive Dual-task Improves Selective Attention - Kunzler, Marcos Roberto; Carpes, Felipe P. (International Journal of Sports Medicine, 2022)
Physical and cognitive exercises have positive long-term effects on cognitive capacities. However, acute effects still are controversial. Here we determine the acute effects of physical exercise combined with concurrent cognitive exercise on cognitive performance in young adults. Simple reaction time, selective attention, and memory were evaluated in 23 young men before and after 30 min of stationary cycling exercise, 30 min of stationary cycling exercise combined with cognitive exercise, and 30 min of rest. Exercise intensity was continuously controlled to ensure exercise at moderate intensity. We found that physical exercise combined with cognitive dual-task improves selective attention. Both exercise conditions showed similar effects on simple reaction time, and memory was not affected by the different exercise conditions. We conclude that the combination of cycling exercise at moderate intensity with a cognitive exercise acutely improves selective attention in young adults. These results can be of particular interest for interventions aiming at improving selective attention in sports and for older adults and individuals with difficulty to suppress and filter out task-irrelevant information, like when receiving instruction or learning a new task or concept.
Keywords: physical exercise; dual-task; acute effort; cognition